Outcome After Ruptured AAA Repair in Octo- and Nonagenarians in Sweden 1994–2014. (May 2017) - Sonesson, B.; Björses, K.; Dias, N.; Rylance, R.; Mani, K.; Wanhainen, A.; Resch, T.
Abstract : Objective: To report the outcome after ruptured abdominal aortic aneurysm (rAAA) repair in octo- and nonagenarians from the Swedish Vascular Registry 1994–2014. Material and methods: 2335 intact AAA (iAAA) and 1538 rAAA were identified in patients aged 80 years and older. Crude, long-term, and relative survival data were analysed using the Kaplan-Meier method. Crude survival was calculated including all deaths. Long-term survival was analysed excluding AAA repair related mortality, defined as death within 90 days of surgery. Relative survival was assessed by comparing the observed long-term survival after AAA repair with the expected survival of a Swedish population adjusted for age, gender, and operation year. Differences were compared using log-rank tests. The multivariate Cox model was used for adjusting for confounding factors between open repair (OR) and endovascular aneurysm repair (EVAR). Results: Crude survival after rAAA repair was 30 days (55%), 90 days (50%), 1 year (45%), 5 years (26%), and 10 years (9%). Long-term survival was 1 year (90%), 5 years (53%), and 10 years (18%). When individuals with rAAA were categorized into males and females, crude and long-term survival showed no significant differences ( p  = .204 and p  = .134). When rAAA patients were categorized into age groups (80–84 years, 85–89 years, 90+) crude survival diminished with increasing age, but long-term survival was not ( p  = .009 and p  = .368). Compared with the general population, rAAA patients showed only a minor decrease in relative survival. Crude survival after rAAA was better for EVAR compared with OR ( p  = .007), hazard ratio 1.3 (95% CI 1.1–1.6, p  < .012). Conclusions: There is a high (50%) peri-operative mortality after surgery for rAAA in octo- and nonagenarians, with no significant differences between the sexes and worse survival with increasing age. However, if a patient has survived the initial 90 days, long-term survival in this very old cohort is surprisingly good at more than 50% after 5 years, only slightly less than the general population.